2021
DOI: 10.1002/col.22651
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of colors in food packaging: A study of industrialized products sold in Brazil

Abstract: Currently, packaging needs to communicate material and immaterial qualities of food, linked to the satisfaction of nutritional, psychological and cultural needs of consumers. For this, the design builds complex discourses, associating verbal and visual language. In Brazil, with the standardization of packaging formats and the growing variety of products, the importance of color in visual communication has expanded. This research aims to explain the system of color meanings in food packaging sold in Brazil, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 7 publications
0
7
0
10
Order By: Relevance
“…Packaging is usually a consumer's first interaction with the product (Lemon, 2019). Packaging communicates directly to the customer about price, quality, manufacturing or expiry date and indirectly through its graphics, font styles and images (Pereira, 2021). Packaging and labels motivate potential buyers to buy the product and make the customer trust a particular brand (Kauppinen-Räisänen and Jauffret, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Packaging is usually a consumer's first interaction with the product (Lemon, 2019). Packaging communicates directly to the customer about price, quality, manufacturing or expiry date and indirectly through its graphics, font styles and images (Pereira, 2021). Packaging and labels motivate potential buyers to buy the product and make the customer trust a particular brand (Kauppinen-Räisänen and Jauffret, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Through repeated exposure, consumers form perceptions based on cultural and category codes (Liu and Cheng, 2021). Pereira (2021) used colour semiotics to explain the relevance of colours in food packaging. They concluded that colours represented three semiotic functions: iconic, indicative and symbolic.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In the MC of soft drink packaging, white and warm colors appear more frequently than other colors, and the SC and TC also show the same pattern. Most of these MCs correspond to the color of food, 56 either by reproducing that color in opaque containers, through colored images of the package, or by exposing the liquid itself through a transparent package. In earlier studies on the color of beverage packaging, white symbolizes cleanliness and purity, 68 red, orange, and yellow can cause arousal and excitement 69 .…”
Section: Resultsmentioning
confidence: 99%
“…For the purposes of the analysis that follows, the top three colors that make up the highest percentage of soft drink and spirits product packaging were selected for analysis in these studies. In the following, the color area occupying the largest area in the product is the main color (MC), followed by the secondary color (SC, the one occupying the second largest area) and the third color (TC, occupying the third largest area) 55,56 …”
Section: Research Objects and Methodsmentioning
confidence: 99%
“…Por otro lado Steenis et al, ( 2017), mencionan que el envase tiene el poder para dar forma a las percepciones de los productos. Ambrose y Harris (2011) mencionan que los principales componentes del diseño son el material, la forma y ergonomía, el color, el lenguaje, la tipografía y la fotografía; el color es un factor importante para reconocer la marca, con el paso del tiempo el consumidor puede identificar el producto por un determinado color, aunque García-Madariaga et al, (2019) señalan que la modificación del color de un empaque no tiene un efecto significativo en los niveles de atención del consumidor; pero si el color del envase refleja la heterogeneidad de los grupos de consumidores como por el ejemplo el uso del color blanco para personas sanas o el color rosado para las mujeres (Pereira, 2021).…”
unclassified